Agricultural commercialization in borderlands: Capturing the transformation of a tropical forest frontier through participatory mapping - Latthachack, Phokham; Llopis, Jorge C.; Heinimann, Andreas; Thongmanivong, Sithong; Vongvisouk, Thoumthone; Messerli, Peter; Zaehringer, Julie G. (Frontiers in Sustainable Food Systems, 2023)
Forest-frontier landscapes in the humid tropics display distinct land use change dynamics compared to other world regions, providing useful examples of current global environmental and development challenges. In northwestern Laos, part of the former Golden Triangle region, investments in value chains for commercial crops – mainly to fulfil Chinese market demands – have triggered various land use changes and put increasing pressure on remaining biodiverse forest areas. Capturing the existing land use change trajectories is a key initial step towards further studies assessing land use change impacts. However, methodological challenges arise when conducting spatially-explicit change assessments in these regions, given the high temporal variability of land use at the plot level, compounded by the paucity of good quality satellite imagery. Thus, we applied a novel approach combining analysis of very high-resolution (VHR) satellite imagery with participatory mapping. This enabled joint collection of annual land use information for the last 17 years together with local land users, shedding light on temporally dense land system dynamics. For decades, the government of Laos has sought to halt shifting cultivation, labelling it environmentally degrading, and to reduce poverty through promotion of permanent commodity-oriented commercial agriculture. Among other things, this gave rise to a boom in banana and rubber investments in Luang Namtha province in order to satisfy growing Chinese demand for these commodities. The present paper investigates the impact of these cash crop booms on land use transitions and whether they reduced pressure on forest-frontier areas, as ostensibly desired by government authorities. Our study is among the first to demonstrate in a spatially-explicit manner that subsistence agriculture – in less than two decades – has virtually disappeared in northern Laos due to diverse cash-crop production and agricultural commercialization initiatives linked to Chinese investments. As subsistence-focused cultivation systems are being replaced by land uses solely aimed at commercial production for export, a telecoupled land system is being developed in northwestern Laos with potentially manifold impacts for sustainable development.